Middle Anisian (Bithynian to Illyrian?, Middle Triassic) Ammonoidea from Rüdersdorf (Brandenburg, Germany) with a revision of Beneckeia Mojsisovics, 1882 and notes on migratory pathways - Siegel, Frank; Wiese, Frank; Klug, Christian (Bulletin of geosciences, 2022)
Bithynian and Pelsonian (Anisian, Middle Triassic) Ammonoidea are generally rare in the Germanic Basin. Here, we describe ammonoids from the Jena and Rüdersdorf formations (Lower Muschelkalk) of Rüdersdorf (Brandenburg, Germany). This locality is peculiar in its isolated situation and its comparatively high diversity in ammonoids.
Gesehen am 25.10.2022